KEGIATAN KERJA BAKTI DAN PENANAMAN TANAMAN OBAT DALAM MENUMBUHKAN KESADARAN MASYARAKAT TERHADAP KESEHATAN LINGKUNGAN - Novritsar Hasitongan Pakpahan; Ahmad Alwin Faruq; Didit Darmawan; Moch. Rio Faizal; Rio Saputra (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
This community service activity aims to increase the awareness of residents in Simo Mulyo Baru, Surabaya, regarding the importance of maintaining environmental cleanliness and health. The main issues faced are the low level of community participation in maintaining the environment and the underutilization of vacant land around residential areas. Through the Asset-Based Community Develo pment, approach, this program encourages residents to utilize existing potentials, such as the spirit of mutual cooperation and available land, to conduct community clean-up activities and the planting of family medicinal plants. The results show an increase in residents’ awareness and responsibility in creating a clean and healthy environment. The planting of medicinal plants such as ginger, turmeric, and basil also provides natural health benefits for the community. This activity serves as an example that asset-based empowerment can create positive and sustainable changes within the community environment. This activity shows that community empowerment through the ABCD approach has proven effective in building environmental awareness and fostering responsible, sustainable behavior among the community.